Boundedness of High Order Commutators of Riesz Transforms Associated with Schrödinger Type Operators (Analysis in Theory and Applications, 2022)
Let $\mathcal{L}_2=(-\Delta)^2+V^2$ be the Schrödinger type operator, where $V eq 0$ is a nonnegative potential and belongs to the reverse Hölder class $RH_{q_1}$ for $q_1> n/2, n\geq 5.$ The higher Riesz transform associated with $\mathcal{L}_2$ is denoted by $\mathcal{R}= abla^2 \mathcal{L}_2^{-\frac{1}{2}}$ and its dual is denoted by $\mathcal{R}^*=\mathcal{L}_2^{-\frac{1}{2}} abla^2.$ In this paper, we consider the $m$-order commutators $[b^m,\mathcal{R}]$ and $[b^m,\mathcal{R}^*],$ and establish the $(L^p,L^q)$-boundedness of these commutators when $b$ belongs to the new Campanato space $\Lambda_\beta^\theta(\rho)$ and $1/q=1/p-m\beta/n.$
Keywords: Schrödinger operator; Campanato space; Riesz transform; commutator.